STUDI ETNOMEDISIN PADA MASYARAKAT 5 DESA KECAMATAN SECANG KABUPATEN MAGELANG - Alfian Syarifuddin; Rizka Amalia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
The use of plants for traditional medicines are community tradition in Indonesia. However, the use of plants for hereditary treatment has not been well documented. One of the solutions is an ethnomedicine study, in this study 5 villages located in Secang District, Magelang Regency. The sampling technique used is snowball sampling with observation using instruments and interviews. The number of respondents sample is 388 respondents. The results showed that the community utilized 96 plant species from 47 families. There are 3 types of diseases that use plants in their treatment with an ICF value of 1, namely sprains, nosebleeds, and menstrual flow. The most widely used parts for treatment are leaves (42.61%). The most frequently used processing method is the boiling technique with a percentage of 65.10% by way of use, which is drinking 77.05%. People most often consume with a frequency of 2x a day (74.87%). People usually use treatment during illness/ curative (76.74%). People get plants from their own yard (54.24%). Knowledge about treatment comes from family (hereditary) (72.43%). From some of the results, it can be used as a reference when conducting scientific verification of preclinical testing on test animals.